Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Rumah Sakit Hermina Karawang - Chaerudin, Chaerudin; Anum, Farida (Peneliti.net, 2023)
In : This study uses quantitative methods that are descriptive and causal. The population in this study were all employees of Hermina Karawang Hospital, totaling 187 employees. The sampling technique in this study was Probability Sampling with simple random sampling method. The sample in this study used the Slovin calculation method of 5% so that the sample obtained in this study was 128 employees. Based on the results of the study, the coefficient of determination shows the effect of work motivation on employee performance at Hermina Karawang Hospital by 72.5% while the remaining 27.5% is influenced by other factors not examined in this study. This study concludes that work motivation has a significant influence on employee performance at Hermina Karawang Hospital.